2018
DOI: 10.1186/s13054-018-1962-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal autoregulation and blood pressure management in circulatory shock

Abstract: The importance of personalized blood pressure management is well recognized. Because renal pressure–flow relationships may vary among patients, understanding how renal autoregulation may influence blood pressure control is essential. However, much remains uncertain regarding the determinants of renal autoregulation in circulatory shock, including the influence of comorbidities and the effects of vasopressor treatment. We review published studies on renal autoregulation relevant to the management of acutely ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 83 publications
2
29
0
Order By: Relevance
“…The shear stress will stimulate the proinflammatory response which is present on the surface of endothelial cells, increase the expression of endothelial adhesion molecules and their interactions with neutrophils, monocytes that triggers the release of IL-6. [23][24][25][26][27] Our study showed a higher release of IL-6 during pneumoperitoneum insufflation in the standard pressure group than in the low pressure group. Although CO 2 and surgical techniques can contribute to the release of proinflammatory cytokines, 28 our study showed that an acute, slight increase in intraabdominal pressure results in significantly increased IL-6 levels.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The shear stress will stimulate the proinflammatory response which is present on the surface of endothelial cells, increase the expression of endothelial adhesion molecules and their interactions with neutrophils, monocytes that triggers the release of IL-6. [23][24][25][26][27] Our study showed a higher release of IL-6 during pneumoperitoneum insufflation in the standard pressure group than in the low pressure group. Although CO 2 and surgical techniques can contribute to the release of proinflammatory cytokines, 28 our study showed that an acute, slight increase in intraabdominal pressure results in significantly increased IL-6 levels.…”
Section: Discussionmentioning
confidence: 47%
“…23 The renal perfusion is affected by the blood flow and pressure on blood vessels. 24 The impaired blood flow changes the normal blood flow from laminar into turbulent or oscillatory flow that causes the shear stress. The shear stress will stimulate the proinflammatory response which is present on the surface of endothelial cells, increase the expression of endothelial adhesion molecules and their interactions with neutrophils, monocytes that triggers the release of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The gain quantifies to which extend a change in RBF is caused by a change in RPP. A low transfer gain value implies that oscillations in RPP do not translate into flow fluctuations of similar frequency, that is the kidney is effectively autoregulating in the given frequency band (Post & Vincent, ). The phase indicates the latency between the RBF and RPP signal.…”
Section: Methodsmentioning
confidence: 99%
“…Besides RPP, the influence of β‐blockers on RBF is further complicated by the unknown effect on renal autoregulation in sepsis or septic shock. Renal autoregulation is mediated by vascular reactivity, unlinking RPP from RBF (Post and Vincent, ()). In health, renal autoregulation keeps blood flow at a constant level at perfusion pressures greater than approximately 60–100 mmHg, depending on species (Post, Kellum, Bellomo, & Vincent, ).…”
Section: Introductionmentioning
confidence: 99%
“…What is less well established is the lower limit of MAP beyond which autoregulation breaks down, and when flow becomes directly proportional to the perfusion pressure. Our understanding is currently based on studies of animals , but there appears to be no clear point at which autoregulation ‘breaks down’ (Fig. ) .…”
Section: Renal Perfusionmentioning
confidence: 99%